Bloodstream infections in patients living with HIV in the modern cART era - Taramasso, L. (Sci Rep, 2019)
Retrospective multicentre study aiming at analysing the etiology, characteristics and outcome of bloodstream infections (BSI) in people living with HIV (PLWHIV) in an era of modern antiretroviral therapy. Between 2008 and 2015, 79 PLWHIV had at least 1 BSI, for a total of 119 pathogens isolated. Patients were mainly male (72.1%), previous intravenous drug users (55.7%), co-infected with HCV or HBV (58.2%) and in CDC stage C (60.8%). Gram-positive (G+) pathogens caused 44.5% of BSI, followed by Gram-negative (G−), 40.3%, fungi, 10.9%, and mycobacteria, 4.2%. Candida spp. and coagulase-negative staphylococci were the most frequent pathogens found in nosocomial BSI (17% each), while E.coli was prevalent in community-acquired BSI (25%). At the last available follow-up, (mean 3.2 ± 2.7 years) the overall crude mortality was 40.5%. Factors associated with mortality in the final multivariate analysis were older age, (p = 0.02; HR 3.8, 95%CI 1.2–11.7) CDC stage C (p = 0.02; HR 3.3, 95%CI 1.2–9.1), malignancies, (p = 0.004; HR 3.2, 95%CI 1.4–7.0) and end stage liver disease (p = 0.006; HR 3.4, 95%CI 1.4–8.0). In conclusion, the study found high mortality following BSI in PLWHIV. Older age, neoplastic comorbidities, end stage liver disease and advanced HIV stage were the main factors correlated to mortality.